Ascaris lumbricoides causing jejunal perforation after trivial trauma - Tejareddy, Kandula Venkata; Babu, A. Venkanna; Varma, K. Deepak; Singh, D. Bal (International Surgery Journal, 2017)
Ascariasis is one of the most common parasitic illnesses in human beings living in underdeveloped and developing countries. Infestation with this can result in wide range of manifestations. Most are asymptomatic, very few patients may develop complications like obstruction, perforation, cholangiohepatitis, pancreatitis, etc. We came across a patient, 20-year-old male who presented to the emergency department with acute abdomen followed by trivial trauma, investigations lead to peritonitis as diagnosis. On emergency laparotomy, unexpectedly Ascaris worms wriggling through jejunal perforation and live adult worms freely floating in peritoneal cavity were seen. It is suggested that trivial trauma might have exacerbated impending Ascaris perforation. A jejunal perforation of Ascaris after trivial trauma is a rare entity. This unique case has highlighted the fact that Ascaris can lead to intestinal perforation in heavily infested individuals particularly in tropical countries following trivial trauma.